ANALISIS YURIDIS PENANGGULANGAN TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN UNTUK MEWEUJUDKAN KEAMANAN MASYARAKAT (PENELITIAN DI KEPOLISIAN RESOR NATUNA) - Eric Rianto Eliezer; Simatupang Ramlan; Ramon Nofrial (Ensiklopedia of Journal, 2022)
Crime comes from the Latin word crimen which means crime. One of the crimes that have befallen society lately is theft. Theft is divided into several types, one of which is theft with tampering. The crime of theft by weight is regulated in the Criminal Code. With the case of theft with weighting that occurs, it is necessary to have a countermeasure which is the enforcement of criminal law. The formulation of the problem in this study is how the legal arrangements regarding the prevention of the crime of theft by weighting and what the implementation of the crime of theft by weighting is carried out by the Natuna Resort Police. The research method used in this research is normative legal research or library research and empirical research or field research. Based on the results of the study, legal arrangements regarding forms of crime prevention can be seen in the Criminal Procedure Code as contained in Chapter 5 part 1 (Arrest), part 2 (Detention), and part 4 (Confiscation). Meanwhile, the prevention of criminal acts carried out by the National Police can be seen in Article 14 paragraph 1, Article 15 paragraph 1, and Article 16 of Law Number 2 of 2002 concerning the Indonesian National Police. The efforts made by the Natuna Resort Police are making efforts, namely repressive countermeasures and preventive countermeasures.Keywords: Theft, weighting, crime, countermeasure